Brav3let / Nurul Jannah Fatehah Kamarul Zaman … [et al.] - Kamarul Zaman, Nurul Jannah Fatehah; Mohd Samsuri, Nur Zarif Sofea; Azman, Aina Faqihah; Ayub, Nur Anis; Azman, Muhammad Rusydi; Wan Hasan, Wan Hasmat (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Brav3let is a brand that provide a bundle of multi-function bracelet design for women and kids. The design was made with safety features that can prevent the customers from harm while stay fashionable. The alarm, GPS and laser has been designed and maintained by Brav3let engineers to ensure user’s safety anywhere and anytime. The alarm that has been set in this bracelet are used to scare the attackers and attract attention from people around especially when your kids or women go out alone. Moreover, the GPS tracker also has been set with a small button behind for acquaintances to know where the latest locations are anywhere and anytime. This bracelet also equipped with a laser that may be fired to the kidnapper or anyone else's eyes. For this reason, direct or reflected lasers can inflict irreversible eye damage with a single glimpse, as the eyes are far more sensitive to light. Taking a closer look at things that happening nowadays which is the case of snatch or abductor, or others were high. Most of this case usually involve women and children only because both are easily targeted due to their weak nature. So, we make this bracelet to avoid this case happens again and also reduce this case in the future. As technology advances, Brav3let's long-term plan is to focus on safety while prioritizing fashion. We intend to see Brav3let on every woman and child in the near future because of our affordable prices and for the safety itself.